The Role of Voltage-Gated Sodium Channel 1.8 in the Effect of Atropine on Heart Rate: Evidence From a Retrospective Clinical Study and Mouse Model - Liu, Baowen; Li, Ningbo; Zhang, Jin; Liu, Yi; Zhang, Mi; Hong, Yishun; Wu, Wenyao; Zhang, Xianwei; Duan, Guangyou (Frontiers in Pharmacology, 2020)
Atropine is commonly used to counter the effects of the parasympathetic neurotransmitter acetylcholine on heart rate in clinical practice, such as in the perioperative period; however, individual differences in the response to atropine are huge. The association between SCN10A/voltage-gated sodium channel 1.8 (NaV1.8) and cardiac conduction has been demonstrated; however, the exact role of SCN10A/NaV1.8 in the heart rate response to atropine remains unclear. To identify the role of SCN10A variants that influence the heart rate responses to atropine, we carried out a retrospective study in 1,005 Han Chinese subjects. Our results showed that rs6795970 was associated with the heart rate response to atropine. The heart rate responses to atropine and methoctramine in NaV1.8 knockout mice were lower, whereas the heart rate response to isoproterenol was like those in wild type mice. Furthermore, we observed that the NaV1.8 blocker A-803467 alleviated the heart rate response to atropine in wild type mice. The retrospective study revealed a previously unknown role of NaV1.8 in controlling the heart rate response to atropine, as shown by the animal study, a speculative mechanism that may involve the cardiac muscarinic acetylcholine receptor M2.